Ecological Study of a Medicinal Orchid (Satyrium Nepalense) in an Alpine Meadow - Paudel, Babu Ram; Poudel, Brihaspati (Himalayan Biodiversity, 2019)
Ecological study of a plant species provides a valuable insight on the current status and potential future threats of the plant species. In this study, we assessed the ecological status of a medicinal orchid, Satyrium nepalense in a pasture land distributed between the elevations of 2600-3200 m asl. We then assessed the current threat status of the orchid based on the standards set by the world conservation union (IUCN) red list categories and criteria version 12. Our result revealed that this orchid preferably grows in the south facing open meadow. We found that in the present condition, the population of S. nepalense did not fall into any threat category. Indiscriminate harvesting of this plant as a fodder together with other grasses during its flowering phase is the main future potential threat to this valuable orchid at the study site. Educating local people about the ecology and importance of this medicinal orchid could prevent its future depletion from the wild habitat.